The Role of Vertebral Body Tethering in Treating Skeletally Immature Scoliosis. Issue 1 (February 2022) - Meza, Blake C.; Samuel, Andre M.; Albert, Todd J.
This is a critical analysis of a study by Hoernschemeyer et al, "Anterior Vertebral Body Tethering for Adolescent Scoliosis with Growth Remaining: A Retrospective Review of 2 to 5-Year Postoperative Results" ( J Bone Joint Surg Am, 2020;102[13]:1169–1176), that assessed the clinical and radiographic outcomes of vertebral body tethering (VBT) in the treatment of adolescent scoliosis. The authors demonstrated successful treatment in 74% of patients, based on radiographic outcomes and avoidance of subsequent posterior spinal fusion. Nearly a quarter of patients required revision surgery. Almost half suffered a broken tether, although the effects of such complications are not fully understood. The study provided valuable information for determining which patients are reasonable candidates for VBT and emphasizes several questions surrounding this novel technology that remain unanswered. This analysis discusses the study's strengths and weaknesses, suggests potential directions of future research, and examines the potential indications for VBT.